The Interactive Role of Emotional Intelligence in the Relationship between Positive Leadership Behaviors and Job Involvement: An Analytical Study of the Opinions of Academic Leaders in Saudi Universities - Alregeb, Tawfeeq Zayed Mohammad (Journal of Educational and Psychological Sciences, 2023)
This study aimed at analyzing the impact of Positive Leadership on Job Involvement through Emotional Intelligence at the Saudi Universities. To achieve the objectives of the study and test its hypotheses, the descriptive analytical method was used. The questionnaire was used as a main tool for data collection. The study sample consisted (analysis unit) of 210 leaders of academic leaders in Saudi Universities. The results of the study found that there was a significant impact of Positive Leadership on Job Involvement, there was a statistically significant impact of Positive Leadership on Emotional Intelligence, there was a Significant impact of Emotional Intelligence on Job Involvement, and there was an indirect impact of Emotional Intelligence as a moderating variable in the relationship between Leadership Positive and Job Involvement. The study recommended the need to develop the skills and resources of Positive Leadership among leaders in accordance with the main objectives of Saudi Universities.
Keywords: Emotional Intelligence; Positive Leadership; Job Involvement; Academic Leaders; Saudi Universities; Study